1996
DOI: 10.1177/000348949610500408
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Evoked Otoacoustic Emissions in a Child with Bilateral Profound Hearing Loss

Abstract: Recording of bilateral evoked otoacoustic emissions in a 3-year-old girl with bilateral profound hearing loss is presented. No component of auditory-evoked brain stem potentials was recorded. Findings on computed tomography of the inner ear were within normal limits. At retest 3 months later, these results were unchanged. Explanations for this particular condition are presented together with a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Clearly, noncochlear patterns of DPOAEs are not specific for acoustic neuromas or, for that matter, any IAC or CPA tumors, since a variety of pathological processes has been shown to result in OAEs suggestive of a peripheral auditory disconnection syndrome. 20–31,52,53 In fact, OAEs may be normal in the presence of severe behavioral thresholds in cases of nonorganic, or functional, hearing loss. 54 OAEs seem to be specific to outer hair cell function, suggesting that some noncochlear patterns may be obtained from ears with hearing loss‐related inner hair cell loss or, perhaps, even dysfunction in other cochlear structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly, noncochlear patterns of DPOAEs are not specific for acoustic neuromas or, for that matter, any IAC or CPA tumors, since a variety of pathological processes has been shown to result in OAEs suggestive of a peripheral auditory disconnection syndrome. 20–31,52,53 In fact, OAEs may be normal in the presence of severe behavioral thresholds in cases of nonorganic, or functional, hearing loss. 54 OAEs seem to be specific to outer hair cell function, suggesting that some noncochlear patterns may be obtained from ears with hearing loss‐related inner hair cell loss or, perhaps, even dysfunction in other cochlear structures.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been studies of both TEOAEs 32–42 and (to lesser extent) DPOAEs 43–45 in patients with acoustic neuromas, the comparisons between OAEs and behavioral thresholds have been subjective and nonuniform. Furthermore, although the authors of these investigations concluded that OAEs were not very sensitive, the results of these studies, and of the central auditory pathology case reports, 20–31 suggested that OAEs had a high specificity as a screening test for retrocochlear disease, when the emissions were better than expected for the degree of behavioral hearing loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the findings of DPOAEs in patients with profound hearing loss, it has been reported that normal DPOAEs can be observed in deaf patients without any detectable wave in ABR 16‐18 . In those cases, the disorder could be at the level of the inner hair cells (IHCs), synapses between IHCs and the eighth auditory nerve fibers, or any combination thereof.…”
Section: Discussionmentioning
confidence: 99%
“…As for the findings of DPOAEk in patients with profound hearing loss, it has been reported that normal DPOAEs can be observed in deaf patients without any detectable wave in ABR. [16][17][18] In those cases, the disorder could be at the level of the inner hair cells (IHCs), synapses between IHCs and the eighth auditory nerve fibers, or any combination thereof. Based on the present study, in which a particular case showed significant levels of DPOAEs but no apparent auditory nerves in the 3DFT-CISS images, it should be considered that a majority of the cochlear nerve fibers may not be present in such cases of profound deafness with significant OAEs.…”
Section: Discussionmentioning
confidence: 99%